Faktor-Faktor yang Mempengaruhi Pelaksanaan Imunisasi Dasar Lengkap pada Bayi: Factors Affecting the Implementation of Complete Basic Immunization in Infants - Syahdia, Yolanda; Lidya, Metri (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Background: Complete basic immunization is a key public health strategy to prevent infectious diseases in infants, yet immunization coverage remains below national targets in several regions. Various maternal, familial, and service-related factors are believed to influence the implementation of complete basic immunization. This study aimed to analyze factors associated with the implementation of complete basic immunization among infants at the Cempaka 2 Integrated Health Post, Andalas Village. A quantitative cross-sectional study was conducted involving mothers with infants aged 0–11 months. All eligible participants were included using a total sampling technique. Data were collected using structured questionnaires assessing maternal characteristics, attitudes, family support, and health service factors. Statistical analysis was performed using bivariate analysis followed by multivariate logistic regression to identify dominant influencing factors. Results: The findings indicated that several maternal and social factors were associated with the implementation of complete basic immunization. Maternal age, education level, attitude toward immunization, and family support showed significant associations with immunization completeness, while maternal occupation, knowledge level, and perceived quality of health services were not significantly associated. Multivariate analysis identified maternal age as the most dominant factor influencing the implementation of complete basic immunization. The implementation of complete basic immunization is influenced by a combination of maternal and family-related factors. Strengthening health education, fostering positive maternal attitudes, and enhancing family support are essential strategies to improve immunization coverage among infants.